Pacific inflow control on phytoplankton community in the Eastern Chukchi Shelf during summer. (15th October 2016) - Zhuang, Yanpei; Jin, Haiyan; Li, Hongliang; Chen, Jianfang; Lin, Ling; Bai, Youcheng; Ji, Zhongqiang; Zhang, Yang; Gu, Fan
Abstract: Photosynthesis pigments and size-fractionated chlorophyll a were determined during the Chinese CHINARE Arctic cruise in summer 2010, to study the phytoplankton community in response to different Pacific water masses in the Eastern Chukchi Shelf (ECS). In the summer, the phytoplankton biomass was high with large diatoms dominated in the shelf, which might in favor to well-stratified water conditions and adequate nutrient supply of Pacific waters. However, nitrate-poor Alaska Coastal Water (ACW) altered the phytoplankton community structure in the east part of Chukchi shelf, as dinoflagellate and chrysophyte biomass significantly increased. It was shown that in ACW-influenced area, the Chl a concentration was an order of magnitude lower (0.41 µg/dm 3 in averaged) compared to that in the entire ECS, with the community mainly consisting of nano- and pico-phytoplankton. The result indicated that the diatom-dominated shelf was greatly impact by the spreading pathway of ACW. Thus, the future enhancement of ACW and subsequent ecological impact need further concern. Highlights: Pigments and size-fractionated chlorophyll a were determined in the Chukchi Shelf. Phytoplankton biomass was high ascribe to nutrient supply of Pacific waters. Phytoplankton community was greatly impact by nitrate-poor Alaska Coastal Water. Future enhancement of ACW and subsequent ecological impact need further concern.